Adipocyte‐specific disruption of mouse Cnot3 causes lipodystrophy. Issue 2 (12th January 2017) - Li, Xue; Morita, Masahiro; Kikuguchi, Chisato; Takahashi, Akinori; Suzuki, Toru; Yamamoto, Tadashi
Abstract : Lipodystrophy involves a loss of adipose tissue. In mice, disruption of adipose tissue Cnot3, a subunit of the CCR4‐NOT deadenylase complex, causes adipose tissue anomalies. In Cnot3 ad−/− mice, white adipose tissue (WAT) decreases concomitantly with enhanced inflammation, whereas brown adipose tissue increases and contains larger lipid droplets. Cnot3 ad−/− mice show hyperinsulinemia, hyperglycemia, insulin resistance, and glucose intolerance, and cannot maintain body temperature during cold exposure. Increased expression of inflammatory genes and decreased leptin expression also occur in Cnot3 ad−/− WAT, achieving levels similar to those in lipodystrophic aP2‐nSrebp1c and Pparg ldi/+ mice; thus, Cnot3 ad−/− mice exhibit lipodystrophy. Abstract :